The Fixed Point Property of Strong Pseudocontraction Mapping - CUI Yunan; ZHU Peng; WANG Ping (Journal of Harbin University of Science and Technology)
In this paper, the iterative methods of fixed point of strong pseudocontraction mappings and accretive operators are studied in Banach spaces. A new threestep Ishikawa iteration is given. It is proved that the iterative scheme sequence convergent to the fixed point of strong pseudocontraction mapping or accretive operators. Meanwhile, the result mentioned above is extended to n steps of Ishikawa iteration for strong pseudocontraction mappings and accretive operators.